Variation and adaptation of leaf water content among species, communities, and biomes - Ruomeng Wang; Nianpeng He; Shenggong Li; Li Xu; Mingxu Li (Environmental Research Letters, 2021)
Leaf water content (LWC) is essential for the physiological activities in plants, but its spatial variation and the underlying mechanisms in natural plant communities are unclear. In this study, we measured the LWC of 5641 plant species from 72 natural communities in China, covering most terrestrial ecosystems, to answer these questions. Our results showed that LWC, on average, was 0.690 g g ^–1 , and was significantly higher in forests and deserts than in grasslands. LWC was significantly different among different plant life forms, and ranked on averages in the following order: herbs > shrubs > trees. Interestingly, LWC decreased with increasing humidity and increased in dry environments. Furthermore, the variations of LWC in plant communities were higher in arid areas and those species with lower LWC in a plant community were more sensitive to changing environments. These results demonstrated the adaptations of plants to water regime in their habitats. Although, phylogeny has no significant effect on LWC, plant species both in forests and grasslands evolve toward higher LWC. Variations of LWC from species to community to biome represent the cost-effective strategy of plants, where plant species in drier environment require higher input to keep higher LWC to balance water availability and heat regulation. This systematic investigation fills the gaps on how LWC varies spatially and clarifies the different adaptation mechanisms regulating LWC across scales.